Determinants of Effective Caregiver Communication After Adolescent Traumatic Brain Injury. Issue 8 (14th February 2015) - Hobart‐Porter, Laura; Wade, Shari; Minich, Nori; Kirkwood, Michael; Stancin, Terry; Taylor, Hudson Gerry
Abstract: Objective: To characterize the effects of caregiver mental health and coping strategies on interactions with an injured adolescent acutely after traumatic brain injury (TBI). Design: Multi‐site, cross‐sectional study. Setting: Outpatient setting of 3 tertiary pediatric hospitals and 2 tertiary general medical centers. Participants: Adolescents (N = 125) aged 12‐17 years, 1‐6 months after being hospitalized with complicated mild to severe TBI. Methods: Data were collected as part of a multi‐site clinical trial of family problem‐solving therapy after TBI. Multiple regression analyses were used to examine the relationship of caregiver and environmental characteristics to the dimensions of effective communication, warmth, and negativity during caregiver‐adolescent problem‐solving discussions. Main Outcomes Measures: Adolescent and caregiver interactions, as measured by the Iowa Family Interaction Rating Scales. Results: Caregivers who utilized problem‐focused coping strategies were rated as having higher levels of effective communication ( P < .01), as were those with higher socioeconomic status ( P < .01). Problem‐focused coping style and higher socioeconomic status were also associated lower levels of negative interactions ( P < .01 and P < .05, respectively). Female gender of the adolescent and fewer children in the home were associated with increased parental warmth during the interaction ( P < .01 and P < .05, respectively). Neither adolescent TBI severity nor caregiver depression significantly influenced caregiver‐teen interactions. Conclusions: Problem‐focused coping strategies are associated with higher levels of effective communication and lower levels of caregiver negativity during the initial months after adolescent TBI, suggesting that effective caregiver coping may facilitate better caregiver‐adolescent interactions after TBI.